Management of early-stage metastatic prostate cancer: appraisal of locoregional treatments and radiation therapy, with or without immunomodulation. Issue 8 (15th July 2021) - Sandoval, Maria L; Dohm, Ammoren; Yamoah, Kosj
Abstract : The current standard for the management of locally advanced and early stage metastatic prostate cancer relies on a backbone of androgen deprivation therapy (ADT) combined with radiotherapy (RT), a regimen that at a glance appears relatively straightforward. The emergence of newer diagnostic, genomic and imaging modalities have allowed for better disease risk-stratification and opened avenues for the development of more patient-centered treatment strategies. This review aims to highlight the central role of RT as part of a multi-modal approach and discuss established and emerging data for the management of locally advanced disease, biochemical recurrence, and oligometastatic disease, as well as the use of immunotherapies and radio-isotopes. This review will also briefly discuss ongoing clinical trials that provide new insights into the paradigm shift in the management of locally advanced prostate cancer.